Predictors and methological issues in tracking total body fat mass, trunk fat, mass and abdominal fat mass : changes in a weight loss intervention with overweight and obese women. - Branco, Teresa Cristina Lourenço (2012)
Doutoramento em Motricidade Humana, especialidade de Saúde e Condição Física